A Rare Reason for Pelvic Pain in Pregnancy: Infectious Sacroiliitis - Yasemin Cekmez; Ahmet Göçmen; Oğuz Arslan; Fatih Şanlıkan; Simge Bağcı Türkmen (Case Reports in Medicine)
Introduction. Although the incidence of pregnancy-associated sacroiliitis is low, it is associated with significant morbidity and mortality. Timely diagnosis of the disease is confusing due to its nonspecific clinical features. Case. A 28-year-old woman at 34 weeks of gestation with severe pain in her right buttock radiating down the backside of the right thigh was admitted to our hospital. White blood cell (WBC) count and C-reactive protein (CRP) were elevated. The pelvic magnetic resonance imaging (MRI) scan revealed right sacroiliitis. Conclusion. Infectious sacroiliitis should be considered as a differential diagnosis even in low-risk women who present with debilitating pelvic pain in pregnancy and medical treatment should not be delayed.